Custody early warning scores; Do they predict patient deterioration in police custody?. (November 2020) - Miles, Tim; Webb, Vanessa; Kevern, Peter; Shibchurn, Raj; Bird, Tom; Finch, George
Abstract: This paper analyses the results of a three month trial based in a police custody suite, where we assigned a value; using the recently developed Custody Early Warning Score, to detainees arriving into police custody, as part of their 'booking in' process. We then compared this to the more established National Early Warning Scoring system and then looked at the predictive accuracy of these two systems and how they correlated to one another, when applied to three different clinical groups of detainees in police custody. Police Custody Sergeants and Custody Detention Officers continue to experience difficulties in identifying those detainees with health care needs; be they subtle, emerging or more evident. The introduction of a 'track and trigger' physiological scoring system has been seen to reduce morbidity in health care settings and so the adoption of an altered custodial version of such a system is an effort by some police forces to do likewise. Recent innovations in police custody have focussed on identifying and appropriately referring those detainees with mental health needs. There is a lack of research that examines the physical health needs of the custodial population and the risks that they might present. With detainee deaths and serious adverse events continuing to occur in police custody, forces are looking at ways to identify risk early on in the custodial process, to reduce such high profile occurrences. Police use of the Custody Early Warning Score system, is one effort to try and identify and reduce this risk, early on in the custodial process. Objective: In an increasing number of police custody suites, the Custody Early Warning Score system has been, added to the normal, standardised police risk assessment process. This 'track & trigger' system has been adapted to the custody environment and is conducted by non-medical detention staff upon detainee arrival, in order to identify detainee morbidity and mortality risk. We wanted to test the predictive accuracy of this system at identifying detainee health need and prioritisation. We also wanted to know how well this tool correlated to another well-established monitoring tool and how accurate these two systems are at pre-empting the medical emergencies and hospital referrals that occur in police custody. Results: 1′163 detainees were assessed by medical staff over a three month period, with staff blinded to the assigned scoring. 276 of these were identified as requiring further clinical assessment following this scoring with 29 of the 33 patients referred to hospital by medical staff, also scored, with some declining assessment or were serious enough to abandon scoring. Whilst we found a small correlation between increased scores and referral to hospital; we found that there was little correlation between assessment scores in general and the need for referral to hospital. We also found that most clinical risk was associated with lower or low scores. Conclusions: The scoring systems that we assessed were not sensitive enough to identify health need in the detainee population, due to frequent, altered physiological parameters. Life threatening conditions have low assessment scores, not reflective of the seriousness of medical conditions, nor the potential for rapid deterioration. Such scoring systems add little to the risk assessment process, with low scores allowing for complacency and a false reassurance, when using a system designed for very different circumstances.